New ideas on how drivers perceive speed emerge from the fog - Culham, Jody C (eLife Sciences Publications, Ltd, 2012)
Experiments with a driving simulator contradict previous results by showing that car drivers slow down in fog. However, other forms of reduced visibility can cause drivers to speed up.